Dimensionality and gender-based measurement invariance of the Compassion Scale in a community sample. (15th October 2017) - Sousa, Rúben; Castilho, Paula; Vieira, Cláudia; Vagos, Paula; Rijo, Daniel
Abstract: Compassion has been proposed as relevant to psychological functioning and mental health, involving being compassionate and caring towards others in times of difficulty. The Compassion Scale (CS) proposes to assess compassion for others considering its different dimensions (Kindness; Common humanity; Mindfulness; Indifference; Separation, and Disengagement) and also offers a total score. The current work investigated the psychometric properties of the Portuguese version of this instrument in adults (N = 610). Results showed the acceptability of a two higher-order factor solution representing a negative and a positive valence of compassion (i.e., Compassion and Disconnectedness), with each higher-order factor comprising three different dimensions of compassion. Multi-group analyses established measurement invariance across gender; further mean comparison analyses showed that women presented higher levels of the positive dimensions of compassion, whereas men showed higher levels of the negative ones. The CS demonstrated good internal consistency, test-retest reliability, and limited validity in relation to external variables. Overall, these findings contribute to the validation of the CS in a non-clinical adult sample, supporting a new measurement model that partially concurs with the original one. It thus provides the user with a new way of assessing and interpreting compassion that may be useful both in research and clinical settings. Highlights: The Compassion Scale (CS) proposes to measure compassion towards others in adults. Alternative measurement models for the CS are investigated and compared. Two higher-order factors plus six first-order factors were the best fit for the data. Strong gender-based measurement invariance was found. Women were found to be generally more compassionate then men.